2014
DOI: 10.17219/acem/37125
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-Coated Polylactic-Glycolic Acid (PLGA) Seeded with Neural-Differentiated Human Mesenchymal Stem Cells as a Potential Nerve Conduit*

Abstract: Background. Autologous nerve grafts to bridge nerve gaps pose various drawbacks. Nerve tissue engineering to promote nerve regeneration using artificial neural conduits has emerged as a promising alternative. Objectives. To develop an artificial nerve conduit using collagen-coated polylactic-glycolic acid (PLGA) and to analyse the survivability and propagating ability of the neuro-differentiated human mesenchymal stem cells in this conduit. Material and Methods. The PLGA conduit was constructed by dip-molding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 30 publications
(35 reference statements)
1
24
0
Order By: Relevance
“…Due to the easy controlling of mechanical properties and biodegradation, PLGA is one of the top biodegradable synthetic polymers used for tissue engineering, especially neural tissue engineering8. It has been used as carrier for various cells to restore injured nerve910. Among the cells, Schwann cells (SCs) which can stimulate the axonal growth, myelinate regenerating axons and reduce cyst formation and secondary damages to the tissue are promising11.…”
mentioning
confidence: 99%
“…Due to the easy controlling of mechanical properties and biodegradation, PLGA is one of the top biodegradable synthetic polymers used for tissue engineering, especially neural tissue engineering8. It has been used as carrier for various cells to restore injured nerve910. Among the cells, Schwann cells (SCs) which can stimulate the axonal growth, myelinate regenerating axons and reduce cyst formation and secondary damages to the tissue are promising11.…”
mentioning
confidence: 99%
“…Therefore, collagen also received much attention in bone tissue engineering. To enhance the bioactivity of collagen hydrogels for bone regeneration, different strategies were explored in recent years, such as supplementing collagen with other bioactive materials or growth factors [31,32]. In the present study, we demonstrated that PPARγ inhibiting with siRNA together with bFGF could synergistically promote MSC osteogeneic differentiation.…”
Section: Discussionsupporting
confidence: 51%
“…Also, collagen supports cell proliferation and tissue regeneration [65,73,104]. As nerve conduits collagen allows the establishment of topographical cues that guide axons to regrow [105,106] and has shown excellent cell adhesive properties that encourage cell attachment and proliferation [106,107]. The degradation time of the collagen conduits is relatively prolonged and takes up to 48 months which can cause nerve compression and fibrosis [84].…”
Section: Collagenmentioning
confidence: 99%